Disability and human rights : global perspectives - Garcia-Iriarte, Edurne; McConkey, Roy; Gilligan, Robert, 1954- (London ; New York, NY : Palgrave Macmillan, 2016)
"This book provides a rich exploration of disability across key areas of human rights- from health and education to independent living- and demonstrates how they are integral to achieving equality for disabled people. Comprehensive and accessible it draws on cutting edge international research and real life examples from across the globe"--
1. Disability and Human Rights in a Global Age / E. Iriarte, R. McConkey and R. Gilligan -- 2. Models of Disability / E. Iriarte -- 3. The UN Convention on the Rights of Persons with Disabilities: Implementing a Paradigm Shift / P. Mittler -- 4. Advocacy and lobbying: The Road Map from Charity to Human Rights / J. Malinga and T. Gumbo -- 5. Global Cultures and Understandings of Disability / A. Gargett, R. Barton, G. Llewellyn, A. Tsaputra, S. Soe and S. Tawake -- 6. Disability, Social Exclusion and Poverty / S. Ghosh, S. Dababnah, S. Parish and L. Igdalsky -- 7. War and Disability: Stories of Dread and Courage / F. Balcazar and D. Balcazar -- 8. Children's rights and disability / R. Gilligan -- 9. Access to Education: Experiences from South Africa / N. Muthukrishna, P. Morojele, J. Naidoo and A. D'amant -- 10. Disability and Inclusive Health / M. MacLachlan, H. Mannan and J. McVeigh -- 11. Assistive Technology and Disability / E.B. Garcia -- 12. Access to Livelihoods / P. Coleridge -- 13. Independent Living in Developing Countries / K. Lamichhane -- 14. People with Disabilities Entering the Third Age / P. McCallion and M. McCarron -- 15. Supporting Family Carers / R. McConkey -- 16. Equipping Professionals with Competencies to Better Support Persons with Disabilities / H. Cornielje and D. Tsengu -- 17. Research training and the Organizational Politics of Knowledge: Some Lessons from Training Disabled Researchers in Southern Africa / L. Swartz.
Includes bibliographical references and index.
Keywords: People with disabilities -- Developing countries; People with disabilities -- Developing countries -- Social conditions; Human rights -- Developing countries; Social science -- Developing Countries; Human rights; People with disabilities; People with disabilities -- Social conditions; Developing countries